2019
DOI: 10.1186/s13036-019-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrical energy storage with engineered biological systems

Abstract: The availability of renewable energy technologies is increasing dramatically across the globe thanks to their growing maturity. However, large scale electrical energy storage and retrieval will almost certainly be a required in order to raise the penetration of renewable sources into the grid. No present energy storage technology has the perfect combination of high power and energy density, low financial and environmental cost, lack of site restrictions, long cycle and calendar lifespan, easy materials availab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 154 publications
(193 reference statements)
0
18
0
Order By: Relevance
“…While the number of electrons needed to produce a molecule of fuel is higher, the whole-cell voltage in an EET-mediated system is lower than in a H 2 -mediated system (∆U cell ≥ 1.23 V for H 2 but only ≥ 0.92 V for EET) as the redox potential of Mtr is much lower than H 2 [26]. Furthermore, the bias voltages at lab-scale remain approximately the same [7], meaning more total current is available to an EET-mediated system. However, EET-mediated electromicrobial production is approximately twice as sensitive to changes in transmembrane voltage than a H 2 -mediated system (Fig.…”
Section: Eet Matches the Efficiency Of H 2 And Can Achieve High Efficiencies At Small Scalesmentioning
confidence: 97%
See 2 more Smart Citations
“…While the number of electrons needed to produce a molecule of fuel is higher, the whole-cell voltage in an EET-mediated system is lower than in a H 2 -mediated system (∆U cell ≥ 1.23 V for H 2 but only ≥ 0.92 V for EET) as the redox potential of Mtr is much lower than H 2 [26]. Furthermore, the bias voltages at lab-scale remain approximately the same [7], meaning more total current is available to an EET-mediated system. However, EET-mediated electromicrobial production is approximately twice as sensitive to changes in transmembrane voltage than a H 2 -mediated system (Fig.…”
Section: Eet Matches the Efficiency Of H 2 And Can Achieve High Efficiencies At Small Scalesmentioning
confidence: 97%
“…We are moving towards a world of plentiful renewable electricity [1][2][3]. However, to enable high penetration of renewables onto the grid, energy storage with a capacity thousands of times greater than today's will be essential [4][5][6][7]. Despite significant advances in electrified transportation, the need for hydrocarbons in many applications like aviation could persist and even grow for decades to come [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromicrobial production technologies aim to combine the flexibility of CO2-fixing and C1assimilating microbial metabolism for the synthesis of complex, energy dense organic molecules from CO2 and renewable electricity [1][2][3][4][5][6] . Already, the Bionic Leaf device has demonstrated that technologies of this class could dramatically exceed the efficiency of photosynthesis 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…A significant advancement in the groundwork and processing of multifunctional hybrid nanomaterials has resulted into the energy storage solutions to address the different challenges. These challenges include high energy and power densities, high power conversion efficiency, long-term stability, and low-cost processes (Zhao et al 2018;Seok et al 2019;Salimijazi et al 2019). The hybridization of these nanomaterials can lead to unique superior multifunction and thus offers the industrial applications in chemical and biological sensing, heterogeneous catalysis, energy conversion and storage, environment, and human health Hu et al 2019).…”
Section: Introductionmentioning
confidence: 99%